Proliferation Marker (Ki67) in Sub-Categorization of Neuroendocrine Tumours of the Lung - Rashi GARG; Amanjit BAL; Ashim DAS; Navneet SINGH; Harkant SINGH (Federation of Turkish Pathology Societies, 2019)
Objective: The 2015 WHO classification classifies neuroendocrine tumours (NET) of the lung into typical carcinoid, atypical carcinoid, large cell neuroendocrine carcinoma and small cell carcinoma based on morphology alone. Mitosis is the major parameter for this classification, and thus several studies have focused on the role of Ki67 in these tumours but without conclusive results. The aim of the study was to categorize neuroendocrine tumours of the lung based on morphology and to assess the utility of Ki67 in diagnosis. Material and Method: The study included 42 cases (23 biopsies and 19 lobectomy specimens) of neuroendocrine tumours (excluding small cell carcinoma). Haematoxylin & eosin stained sections, immunohistochemistry for neuroendocrine markers and Ki67 were studied. Results: Based on WHO criteria, cases were classified as typical carcinoids (83.3%), atypical carcinoids (12%) and large cell neuroendocrine carcinomas (4.7%). The Ki67 index ranged between 1%-10% (mean 2.6%), 10%-30% (mean 19%), 35%-50% (mean 42.5%) in typical carcinoid, atypical carcinoid and large cell neuroendocrine carcinoma respectively. Using the ROC curve, the cut off value of Ki67 for typical and atypical carcinoids was 7.5% (P value<0.001), and for atypical carcinoid/large cell neuroendocrine carcinoma was 32.5% (P value=0.051). On comparing the size and infiltration pattern (both local and lymphovascular invasion) of tumours in resected specimens, there was no association with the proliferation index (P value >0.05). Conclusion: Morphological features are the gold standard for subtyping of neuroendocrine tumours. Ki-67 is a potentially meaningful marker for sub-categorization of lung NETs, especially in small biopsies. However, the size and infiltrative pattern of the tumours are independent of the proliferation index.